2011
DOI: 10.1021/la203992q
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Loaded and Superparamagnetic Iron Oxide Nanoparticle Surface-Embedded Amphiphilic Block Copolymer Micelles for Integrated Chemotherapeutic Drug Delivery and MR Imaging

Abstract: We report on the fabrication of organic/inorganic hybrid micelles of amphiphilic block copolymers physically encapsulated with hydrophobic drugs within micellar cores and stably embedded with superparamagnetic iron oxide (SPIO) nanoparticles within hydrophilic coronas, which possess integrated functions of chemotherapeutic drug delivery and magnetic resonance (MR) imaging contrast enhancement. Poly(ε-caprolactone)-b-poly(glycerol monomethacrylate), PCL-b-PGMA, and PCL-b-P(OEGMA-co-FA) amphiphilic block copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 53 publications
1
73
0
Order By: Relevance
“…[2,3] Also, they can improve the solubility of poorly water-soluble anticancer drugs by encapsulating them into the hydrophobic reservoirs. [4,5] However, despite their advantages in tumor treatment, there are still obstacles limiting clinical applications such as low tumor targetability and poor stability in vivo. [6] In attempts to surmount the problems of conventional polymeric nanoparticles (PNPs), natural polysaccharides such as chitosan, chondroitin, dextran and hyaluronic acid (HA) have been studied as the drug delivery carrier for tumor treatment because they have the benefits of being biocompatible, biodegradable and non-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Also, they can improve the solubility of poorly water-soluble anticancer drugs by encapsulating them into the hydrophobic reservoirs. [4,5] However, despite their advantages in tumor treatment, there are still obstacles limiting clinical applications such as low tumor targetability and poor stability in vivo. [6] In attempts to surmount the problems of conventional polymeric nanoparticles (PNPs), natural polysaccharides such as chitosan, chondroitin, dextran and hyaluronic acid (HA) have been studied as the drug delivery carrier for tumor treatment because they have the benefits of being biocompatible, biodegradable and non-inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…From the slope of 1/T2 vs particle concentration curves, we estimated CNA-IONP relaxivities to be 70, 63 and 73/s/mM Fe in water, PBS and cell culture medium, respectively. Previous research showed that IONPs have T2 relaxivities around 30 /s/mM Fe (18, 43, 64). Contrast efficiency was considerably enhanced by CNA-IONPs compared with Citrate-IONPs.…”
Section: Resultsmentioning
confidence: 99%
“…[90] It has been shown that Gadolinium can be chelated with SPIONs for T1- and T2-weighted contrast MRI and this imaged U87-MG tumors in vivo. [91] SPIONs can also serve as a drug delivery platform for MRI guided therapy [9296] . Interestingly, besides T2-weighted imaging, some Fe 3 O 4 based SPIONs were developed with T1-weighted contrast.…”
Section: Theranostic Nanomaterialsmentioning
confidence: 99%